2015
DOI: 10.1016/j.adolescence.2015.10.008
|View full text |Cite
|
Sign up to set email alerts
|

From placement to prison revisited: Do mental health services disrupt the delinquency pipeline among Latino, African American and Caucasian youth in the child welfare system?

Abstract: Racial and ethnic disparities in delinquency among child welfare‐involved youth are well documented. However, less is known about the mechanisms through which these disparities occur. This study explores the extent to which sets of variables predict the occurrence of juvenile delinquency and whether race/ethnicity moderates the strength of the relationships between (1) social, emotional, and behavioral (SEB) problems and delinquency and (2) mental health service use and delinquency. We used a nationally repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…This complex process depends on several factors, which include but are not limited to offense severity, resource availability, and youth needs (Schwalbe et al, 2012). Given the high rates of mental health issues among youth at risk for incarceration, it is critical that programs designed to divert youth with substantial behavioral health needs have a focus on mental health outcomes and improving access to behavioral health supports and services (Garcia et al, 2015; Maschi et al, 2008). The literature on the effectiveness of diversion in reducing recidivism has indicated mixed outcomes.…”
Section: Juvenile Diversionmentioning
confidence: 99%
“…This complex process depends on several factors, which include but are not limited to offense severity, resource availability, and youth needs (Schwalbe et al, 2012). Given the high rates of mental health issues among youth at risk for incarceration, it is critical that programs designed to divert youth with substantial behavioral health needs have a focus on mental health outcomes and improving access to behavioral health supports and services (Garcia et al, 2015; Maschi et al, 2008). The literature on the effectiveness of diversion in reducing recidivism has indicated mixed outcomes.…”
Section: Juvenile Diversionmentioning
confidence: 99%
“…It has been shown that multiple placements for foster care children increase the risk for delinquent behavior and involvement with the juvenile justice system (Garcia et al, 2015). Studies have found a positive relationship between juvenile delinquency and social, emotional, and behavioral problems.…”
Section: Placement Outside the Homementioning
confidence: 99%
“…Underrepresentation of Latinx families suggests inattention to the needs of this group, exacerbates their vulnerability, and risks the safety and well-being of children. Disproportionality and racial treatment disparities have led to longer reunification periods, permanent loss of parental rights, increased fear of government agencies, and systemic bias (Garcia et al, 2015;Rivera, 2002). Most services and policies within the CWS are not aligned to assist and support Latinx families.…”
mentioning
confidence: 99%
“…More recently, Dierkhising and colleagues (2018) found substantial mental health and substance abuse service needs among dually involved youth: About 75% of youth had a diagnosed mental health issue, and approximately half were receiving mental health services when they were arrested. Garcia and colleagues (2015) found that mental health service use decreased the likelihood of engaging in delinquent behavior for Black youth involved in child welfare. These studies point to the importance of understanding how treatment for such issues may be related to the involvement of youth in the child welfare and justice systems.…”
Section: Literature Reviewmentioning
confidence: 99%